Kondisi Ruang Terbuka Hijau di Kawasan Universitas Malahayati dalam Menyerap Emisi Karbon Dioksida dari Kendaraan Bermotor Pasca Pandemi Covid-19 - Rani Ismiarti Ergantara; Nasoetion; Voni Egya Janika (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
Malahayati University (UNMAL) is a place of higher education with an increasing number of students. This results in a high number of vehicles that have the potential to increase carbon dioxide (CO2) emissions.This research aims to determine the amount of carbon dioxide emissions produced by motorised vehicles and the absorption capacity of green open space (RTH) in the UNMAL area after the Covid-19 pandemic. The number of vehicles is calculated to determine the amount of emissions using the method of traffic counting at peak hours in the morning, afternoon and evening for 6 days and calculation of carbon dioxide emissions with Microsoft Excel and carried out based on the Minister of Environment Regulation No. 12 of 2010 and literature studies are used to calculate the absorption capacity of green open space filling trees. The results of this research show that the total emissions from motorised vehicles in the UNMAL area after the Covid-19 pandemic was 36,904.36 g CO2/hour and the absorption capacity of trees in the UNMAL area was 748,006.92 g CO2/hour. Based on the results, the green open space (RTH) in the UNMAL area is still able to absorb CO2. The strategy to further optimise the absorption capacity of motorised vehicles is to maintain plants (watering, pruning and fertilising) and to carry out replanting (replacement/addition) of trees in various areas such as roads, parks, car parks and helipads.